Psychological distress in individuals with irritable bowel syndrome: the roles of body image and self-criticism - Shulamit Geller; Sigal Levy; Ronit Avitsur (Health Psychology and Behavioral Medicine)
Objective: Irritable bowel syndrome (IBS) is a prevalent gastrointestinal disorder associated with reduced quality of life and psychological distress (PD) including anxiety and depression. The mechanisms linking IBS to PD are unclear. Previous studies showed that body image and self-criticism may be contributory factors. Thus, the objective of this study was to test the potential mediating roles of these factors in the relationship between IBS and PD.Method: 507 adults participated, including 142 with IBS (Mean age = 31.9, SD = 11.7), and 365 healthy peers (Mean age = 26.2, SD = 6.4), ranging in age from 18 to 75. The majority of participants were women (78%). Self-report measures assessed IBS status, body appreciation, body dissatisfaction, self-criticism, sociodemographic status, depression, and anxiety. Path analysis tested the hypothesized mediation model.Results: IBS participants reported greater PD, lower body appreciation, higher body dissatisfaction, and higher self-criticism than controls. Body appreciation and self-criticism sequentially mediated the link between IBS status and both depression and anxiety. IBS was associated with reduced body appreciation, which in turn was linked to heightened self-criticism, thereby leading to elevated psychological distress.Conclusion: Results suggest IBS negatively impacts body image appreciation, fostering self-critical judgments that exacerbate psychological symptoms. This study is the first to demonstrate a significant association between body appreciation and IBS, specifically highlighting this relationship. Findings clarify the psychosocial pathways at play in the comorbidity of mental health issues in IBS. Physicians and other health professionals are advised to detect women with IBS who are distressed, and to offer them appropriate intervention to prevent downstream consequences.